The effectiveness of highly active antiretroviral therapy among HIV-infected children in Asian countries - Torsak Bunupuradah (2018)
Worldwide, there are 2.1 million children under 15 years of age living with HIV infection. In the past five years, there has been significant progress in providing antiretroviral therapy (ART) to children in resourcelimited countries. According to the World Health Organization, an estimated 200,000 children were receiving ART by the end of 2007. Objective: To conduct a general review of pediatric ART effectiveness in Asian countries. Methods: Published articles in PubMed and abstracts from the international HIV conferences were searched for articles related to pediatric ART in Asian countries from 1999 up to 2008. Results: Available reports consistently demonstrated beneficial outcomes of first-line antiretroviral therapy, including significant reductions in mortality and hospitalization rates, and good immunological and virological outcomes. However, there were limited data on the availability of second- line ART and the management of children who failed first-line regimens. There was also a need for improved access to early diagnostic testing and treatment in infancy, and more data on ART selection for children exposed to antiretrovirals for prevention of mother to child transmission. Conclusion: The highly active antiretroviral therapy is effective among HIV-infected children in Asia. Strategies for improved diagnosis and implementation of the life-saving antiretroviral programs including second -line ART, throughout Asia is encouraged.